Implementing AI in Developing Teaching Modules to Support the Independent Curriculum - Allifia Sri Cahyani; Atna Akhiryani; Andi Anirah; Annisa Rahma (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The development of Artificial Intelligence (AI) has had a significant impact across various fields, including education. One of its potential applications lies in the development of teaching modules aligned with the principles of the Merdeka Curriculum. This study aims to describe the implementation of AI in the process of designing and developing teaching modules at SMA Bina Insan Palu. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis of teaching modules, and were then analyzed using data reduction, data presentation, and thematic conclusion-drawing techniques. The findings reveal that the use of AI supports teachers in creating more creative, interactive, and contextual learning materials. Moreover, AI facilitates the development of Project-Based Learning (PjBL) relevant to the Pancasila Student Profile and enables the application of varied and adaptive assessments through AI-based questions and interactive quizzes. AI also contributes to enhancing teachers' creativity in designing digital learning media while saving time in preparing teaching modules. However, teachers' limited digital literacy and the need for intensive training remain major challenges in optimizing AI implementation. The study concludes that AI serves as a pedagogical partner in the development of teaching modules, supporting rather than replacing the role of teachers. To ensure AI utilization is aligned with the goals of the Merdeka Curriculum, strategic efforts are needed in the form of improving digital literacy, providing intensive training for educators, and ensuring adequate technological infrastructure